Changing Epidemiology of Bacterial Meningitis Since Introduction of Conjugate Vaccines: 3 Decades of National Meningitis Surveillance in The Netherlands. (28th November 2020) - Koelman, Diederik L H; van Kassel, Merel N; Bijlsma, Merijn W; Brouwer, Matthijs C; van de Beek, Diederik; van der Ende, Arie
Abstract: Background: The epidemiology of acute bacterial meningitis has changed substantially since the introduction of conjugate vaccines. Methods: We analyzed nationwide surveillance data of all cerebrospinal fluid isolates received by the Netherlands Reference Laboratory for Bacterial Meningitis in the Netherlands. We assessed the impact of conjugate vaccines on incidence (defined as episodes per 100 000 population per year) and for different age groups using incidence rate ratios (IRRs), comparing incidence before and after conjugate vaccine introduction. Results: We analyzed 17 393 episodes, of which 5960 episodes (34%) occurred in preschool children (aged 3 months to 4 years). Overall, bacterial meningitis incidence decreased from 6.37 to 1.58 between 1989–1993 and 2014–2019 (IRR, 0.25 [95% confidence interval CI, .23–.26]; P < .001). This decrease was most pronounced in preschool and school-aged children (5–15 years); IRR, 0.10 [95% CI, .09–.12] and 0.08 [95% CI, .06–.10]; both P < .001. The incidence was highest in young infants (<90 days) due to a high incidence of group B Streptococcus and Escherichia coli meningitis (42.48 and 19.49, respectively). Conjugate vaccines effectively reduced the incidence of Haemophilus influenzae type b, Neisseria meningitidis serogroup C, and 10 pneumococcal serotypes (IRRs, .02–.04; P < .001). At the end of the observed period, Streptococcus pneumoniae caused the majority of meningitis cases (829/1616 [51%]), mostly in older adults (aged 45–64 years) and elderly adults (aged ≥65 years; incidence of 1.06 and 1.54, respectively). Conclusions: Conjugate vaccines reduced the burden of bacterial meningitis, especially in children. The efforts for new measures to prevent bacterial meningitis should be focused on neonates and elderly, as the residual rate of disease is still high in these age groups. Abstract : Conjugate vaccines have significantly reduced the incidence of bacterial meningitis, especially in children. The impact of vaccination has been limited by concurrent serotype replacement, and disease replacement by non-vaccine-targeted bacteria. The residual incidence remains high in neonates and the elderly.